New Construction Technology Application of Bricks by Using Organic Waste from Sugar Refinery Industry - Mohamad, Maheera; Chong, Khai Lin; Abidin, Rahimi; Abu, Noor Hidayah; Razali, Mohd Rizal; Taib, Che Azlan; Mohd Yusoff, Yuhainis (2023)
This study focuses on the potentiality of pressmud (sugarcane refinery waste) as fine bio-aggregate in making construction materials. A series of pressmud at different percentage of weight (50%, 40%, 30%, 20% and 10%) were mixed with Ordinary Portland cement to form binary blended cement-pressmud bricks. Several observations on leaching of heavy metals, total of carbon (TC) and compression test were performed to determine the properties of the pressmud bricks comparing to standard brick. Granular and tank leaching test were performed to further investigate on their environmental effects and the tank leaching tests showed almost no leaching in heavy metals for pressmud brick. Leaching of TC was observed in mixed bricks up to 78.57 mg/l. The compression tests proved that cement-pressmud bricks up to 20% weight ratio gave compatible strength as to standard brick which the value is ranging from 17.16 MPa to 23.01 MPa. The weight of the pressmud bricks were also lighter in which the weight of 10% and 20% brick was lesser by 17-23% compared to the standard brick. Thus it can be concluded that pressmud have great potential as bioaggregate in making light-weight and cheaper construction material at suitable ratios.